KOMPARASI PENGARUH PENGGUNAAN METODE GROUP INVESTIGATION TERHADAP PRESTASI BELAJAR SOSIOLOGI SISWA KELAS XI IPS SMA N 2 SUKOHARJO DAN SMA N 2 SURAKARTA - Suludani, Fera Cahyanti (SOSIALITAS; Jurnal Ilmiah Pend. Sos Ant)
Abstract. Fera Cahyanti Suludani K8409024. THE INFLUENCE OF GROUP INVESTIGATION METHOD COMPARISON TOWARD THE XI SOCIAL GRADE OF SMA N 2 SUKOHARJO AND SMA N 2 SURAKARTA ACHIEVEMENT. Thesis: Theacher Learning And Education Faculty. Sebelas Maret University. Juli 2013 The purpose of the research is to find out: (1) The Difference of Group Investigation method Toward the XI Grade of SMA N 2 Sukoharjo and SMA N 2 Surakarta achievement (2) The Influence of Group Investigation method Comparison Toward the XI Grade of SMA N 2 Sukoharjo and SMA N 2 Surakarta sociology achievement. The research is included causa comparison using quantitative approach. The populations are all of the students XI Social Grade of SMA N 2 Sukoharjo and SMA N 2 Surakarta. The samples of the research are the students of students XI Social Grade of SMA N 2 Sukoharjo (4 social mainstreams) and SMA N 2 Surakarta (2 social mainstreams) who get Group Investigation learning. The technique of collecting sample uses multistage cluster random sampling technique. The technique of collecting data uses examination and school document. The hypothesis test uses non parametric test and linier regression analysis. The conclusion of the research: first hypothesis ?there are difference achievement of SMA N 2 Sukoharjo and SMA N 2 Surakarta students?, accepted. This kind of thing is seen from the result of data analysis which show the quarrel from both Z as big as 4.893, and p=0,00; p is smaller than 0,01. Second hypothesis ?the school influences the average of students? achievement?. It is shown in the result of analysis Rxy = 0.615; determinant coefficient=0.378; f regression value as big as 35.838; significant level 0.00. it can be concluded that there is a sharp double correlation between school environment toward the average of students achievement. Key words: school, Group Investigation method, study achievement.